Beyond Administration: How Continuous Quality Improvement Transforms Professional Collaboration and Student Engagement in Elementary Schools - Agus R, Abu Hasan; Rohmatillah, Layli Febrianti; Adeoye, Moses Adeleke; Iliasu, Samuel Femi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the implementation of Continuous Quality Improvement (CQI) in strengthening the culture of academic quality in elementary schools during the Independent Curriculum era. This study uses a qualitative case study design, with data collected from the principal, vice principal, teachers, administrative staff, and students through in-depth interviews, participant observation, and document analysis. The study was conducted in an elementary school implementing CQI, with data credibility ensured through triangulation and member checks. The results show that CQI strengthens the culture of academic quality through three main mechanisms: (1) the development of a collaborative teacher professional learning community; (2) the systematic use of academic data (attendance, grade recap, and learning portfolio) in learning decision-making; and (3) the transformation of supervision into a coaching-based formative process. These practices result in more structured learning, increased student engagement, and more consistent monitoring of learning progress. This study contributes by positioning CQI as a cultural and pedagogical framework, rather than simply an administrative system. In addition, this study recommends strengthening collaboration, data-based evaluation, and formative supervision to sustain academic quality in elementary schools.